Topographic controls on soil organic carbon partitioning and enzyme dynamics in nutrient-poor soils - Liu, Yifei; Rong, Luge; Cheng, Yu; Wang, Mingmin; Min, Shuo; Xiao, Fuyou; Zhang, Zhiqing; Yang, Ziwei; Zhang, Qingsong; Zheng, Xuehao (Frontiers in Microbiology, 2026)
IntroductionUnderstanding the dynamics of soil organic carbon (SOC) in sloping farmlands is critical, as they play a vital role in the global carbon cycle and soil health. Although prior research has focused on physical carbon loss due to erosion, the biological mechanisms by which slope gradients affect microbial carbon cycling remain poorly understood.MethodsSoil samples were collected from maize fields with three slope gradients (30°, 45°, and 60°) across different growth stages. Key indicators were determined as follows: SOC by potassium dichromate oxidation (external heating method); DOC by ultrapure water extraction (1:5 ratio) and organic carbon analyzer; POC by sodium hexametaphosphate dispersion, 53-μm sieving, and chromic acid oxidation; soil Ca2+, Mg2+, and Cl− by EDTA complexometric titration and silver nitrate titration, respectively; invertase (SUC) by 3,5-dinitrosalicylic acid colorimetry; polyphenol oxidase (SPPO) and peroxidase (SPOD) by commercial kits with L-dopa as substrate. Statistical analyses were performed using IBM SPSS 26 (One-way ANOVA with LSD post-hoc test, Pearson correlation analysis) and Origin 2024 (Principal Component Analysis, PCA). Normality of data was verified prior to analysis, and significance was set at P < 0.05.ResultsResults showed that SOC levels decreased with increasing slope steepness, while DOC peaked at 45°. SPPO and SPOD activities (involved in recalcitrant carbon decomposition) were significantly elevated at 60°. SUC activity was positively correlated with DOC, while oxidase activities were positively associated with POC and negatively with Mg2+.DiscussionThis study identifies a critical slope threshold (30°–45°) for DOC loss: DOC availability on steeper slopes stimulates microbial synthesis of SPPO and SPOD, enhancing recalcitrant carbon degradation and potentially intensifying long-term SOC depletion. The identification of this threshold provides insights for designing microbiome-informed strategies to mitigate soil degradation and safeguard ecological security.